Nonlinear dynamic behaviour of fully coupled Spar platform /A.B.M. Saiful Islam - A.B.M. Saiful, Islam (2013)
The offshore industry has moved towards deep water regions due to continuous depletion of oil and gas reserves at shallow to intermediate water depths. Conventional fixed jacket and bottom supported compliant platforms are inefficient for deep water exploration. Attention has therefore shifted to floating production systems. Floating Spar is one of the concepts amongst the floating structure categories. Spar platform is an assemblage of mooring, riser and Spar hull responding in a complex way to aerodynamic and hydrodynamic forces. At deep water, mooring lines/risers contribute significant inertia and damping. Associated nonlinearities compound the problem further. Precise motion investigation of platform is required for integrity and associated costs of Spar hull and mooring lines/risers. Proper dynamics cannot be assessed by conventionally used decoupled quasi-static methods which ignore all or part of the mooring/riser-platform interaction effects. Coupled analysis can capture all the complexities in reliable fashion. Hence, coupled behaviour of Spar Platform under wave, current and wind loading is of great interest. Suitability of Spar platform in Malaysian deep sea and coupled effect of riser deserve essential concern. In the present study, fully coupled integrated Spar-mooring system (NONLIN-COUPLE6D) has been modelled. Using a nonlinear finite element approach, the deep draft Spar (DDS) hull and each catenary mooring line (CML) are simulated in a single assemblage. Spar hull is treated as rigid beam element and CML as hybrid beam element. The mooring lines as an integral part of the system support the spar hull at fairlead and pinned at the far end on the seabed. They partly hang and partly lying on the sea bed. Sea bed is modelled as a large flat surface with a provision to simulate mooring contact behaviour. Mooring line dynamics considers the instantaneous tension fluctuation and damping forces with time-dependent variance of other properties. Essential nonlinearities involved in the system are properly captured. As all the forces on Spar and CMLs act simultaneously, coupled action is achieved. Hence, there is no need of iteratively matching the force, displacement, velocity and acceleration at the fairlead position. The commercial finite element code ABAQUS/ AQUA is found to be suitable for the present study. The selected configuration of coupled Spar platform is analysed under regular wave, severe wave, current force, wind loading as well as Malaysian environment. For moderate wave, Stroke’s 5th order wave theory is chosen, whereas for other cases wave kinematics are computed by Airy’s wave theory. The API RP 2A and Emil Simiu spectrum have been considered for wind forces. Wave and wind characteristics of Malaysian sea are simulated for 100-year storm condition. Effect of sea bed friction is evaluated under Malaysian environment. Stable response analysis is performed by bifurcation technique and Mathieu instability. Integrated Spar-mooring-